O uso público nos parques urbanos e parques naturais de Sorocaba/SP - Kachinski, Kleber Vinícius Barros (2018)
Permanently discussed, the theme environment and nature becomes current in our society. Nowadays as great importance because it has a deep relationship with spheres of action and human interest, such as, work, education, leisure, etc. The topic brings values to all society as well it is influenced by the ruling social, economic and political structure. Environmental conservation and assure its use by the population is a central element to construction programs for the public use of urban parks and natural parks. It is essential to consider local characteristics while ensuring access to non-formal education programs based on culture and leisure practices. In order to collaborate for the discussion in areas related to the parks, the present work target to verify the appropriation of the public spaces in these areas by the population of Sorocaba and, as well as the policy of recreational activities, and the distribution of these areas in the city of Sorocaba. As a methodology, the study was developed through a combination of bibliographical, documentary and field research. As an instrument of data collection, direct observation in 8 city parks (4 delimited - fenced and 4 without physical delimitation - not fenced), with the use of field diaries and semi-structured interviews with visitors. The collected achieved some points like, of safety, the lack of activity policy, followed by improvements in infrastructure and environmental landscaping. There are parks in worse conditions that end up being underutilized and small frequency to the detriment of better-located parks and higher level of income around these parks receive more activities from public power and private initiative, visitors tend to be frequent in use, highlighting activities are more diversified. Although the high number of parks created, it is strongly necessary to rescue an intersectoral public policy, prioritizing environmental education, culture and leisure in the green areas of Sorocaba.